MENTOR COACHING TO HELP PRE-SERVICE TEACHERS IN DESIGNING AN EFFECTIVE LESSON PLAN - Amalia, Lulu Laela; Imperiani, Ernie (Indonesian Journal of Applied Linguistics, 2013)
Abstract: This paper investigates how mentor coaching, which is intended to prepare preserviceteachers of English as a Foreign Language in facing their teaching practices, help themdesign lesson plans. A lesson plan, as Farrell (2002) stated, is a collection or a summary of ateacherâ€™s thoughts about what will be covered during a lesson. This means that before comingto the teaching process, a teacher should prepare systematic steps to be conducted in a class inorder to reach the objective of a lesson. However, most pre-service teachers are confused withthe designing process of lesson plan that is how to articulate the government curriculum intooperational details. For example, they do not know which activities to include in the lessonplan, and they do not understand how to determine indicators or â€œenabling objectivesâ€ (Brown,2007) for assessing studentsâ€™ achievement in the lesson. Therefore, mentor coaching is seen asone of alternatives in helping pre-service teachers. Mentor coaching, as Nolan (2007, cited inZepeda, 2012, p. 165) said, is a â€œstructured process whereby an experienced person introduces,assists, and supports a less-experienced person (the protege) in a personal and professionalgrowth process.â€ In the context of this study, the experienced person refers to the teacher/thelecturer in the class and the less-experienced person in this context refers to the pre-serviceteachers or student teachers. This study used action research as the method. Furthermore, thedata were obtained by distributing questionnaire and collecting pre-service teachersâ€™ lessonplans as well as conducting an interview. In addition, after having designed a lesson plan withmentor coaching technique, the pre-service teachers were asked to reflect the process in orderto gain their perception about the mentor coaching technique. It is important to find whatthey think and feel about this mentor coaching process because it is expected that this type ofcoaching will be useful in helping pre-service teachers to write an effective lesson plan.